Small cell variant of ALK-positive anaplastic large cell lymphoma with primary subcutaneous presentation: A case report. Issue 26 (June 2018) - Jaing, Tang-Her; Chang, Tsung-Yen; Chen, Shih-Hsiang; Wen, Yu-Chuan; Chuang, Wen-Yu; Yang, Chao-Ping
Abstract: Rationale: The rare morphological variant of anaplastic large cell lymphoma (ALCL) may pose a challenge in diagnosis, especially when presentation primarily involves skin lesions. Patient concerns: Here we describe a rare case of small cell variant of ALCL in an 11-year-old girl. Diagnosis: We performed clinical, morphological, and immunohistochemical analyses of developed cutaneous nodules. Interventions: Pathologists should consider this small cell variant in ALCL differential diagnosis, as early and correct diagnosis has important clinical implications. Outcomes: Allogeneic hematopoietic stem cell transplantation appears to be a promising treatment option for small cell variant of ALCL. Lessons: Histological diagnosis of small cell variant of ALCL is challenging among pediatricians because of its low incidence and atypical presentation. We provide a short review of the small cell variant of ALCL to facilitate the diagnosis of this difficult-to-recognize entity.